MATCHING TEACHING STYLES WITH STUDENTSâ LEARNING STYLES (A SURVEY OF INDONESIAN STUDENTSâ HABITS OF LEARNING) - Husin, Saifuddin Ahmad (LET: Linguistics, Literature and English Teaching Journal, 2016)
There are some studies on traditional East Asian learning styles which found that the most popular East Asian learning styles come from the traditional book-centered and grammar-translation method and the students are seen as analytic, visual, field-independent, concrete-sequential, thinking-oriented and reflective styles. The teachers should match their teaching styles with studentsâ learning styles so thatÂ their motivation, performances, and achievements will increase and be enhanced. There are some approaches which can be applied in the classroom, such as diagnosing learning styles and developing self-aware EFL learners, altering the teaching style to create teacher-student style matching, encouraging changes in students behavior and fostering guided style-stretching and providing activities with different groupings.Â In this study, there are also some cases happened when teaching and learning process occurred in the classroom, for example first language interference, lack of cognates, culturally inappropriate materials, different learning expectations, no response, and students reluctant to speak and there are of course some ways to help students to relax and overcome those problems.